The Influence of Brand Awareness, Perceived Quality, Promotion, and Trust on Men’s Skincare Purchase Intention - R Tita Rospita S; Hilmi Aulawi; Novie Susanti Suseno (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
This study investigates the influence of Brand Awareness, Perceived Quality, Promotion, and Customer Trust on Men’s Skincare Purchase Intention in Garut Regency. The research employed a quantitative approach with a cross-sectional survey of 146 male respondents aged 18–45 years, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that all four independent variables significantly affect Purchase Intention, both simultaneously and partially. Brand Awareness strengthens recognition and reduces perceived risk, Perceived Quality reflects consumer judgments of product effectiveness and safety, Promotion through digital media enhances exposure and interest, while Customer Trust emerges as a decisive factor in purchase decisions and loyalty. These findings conclude that the four factors are essential in shaping effective marketing strategies for men’s skincare products, especially in local markets with distinct consumer characteristics.